Perancangan Aplikasi Rawi pada Android Mobile - Siti Zahrotul Fajriyah; Nurul Ilmi; Rana Zaini Fathiyana; Hesmi Aria Yanti; Aisyah Novfitri (Fakultas Teknik Universitas Muhammadiyah Bengkulu, 2025)
The digital transformation has shifted religious literacy consumption patterns towards mobile platforms requiring high accessibility. However, existing Rawi applications are predominantly image-based, limiting display flexibility and readability for users across different ages, especially the elderly. This study aims to design a Rawi application on Android Mobile implementing an offline-first approach to ensure fast and inclusive content access. The research method employs a Mixed Method with Design Thinking, comprising Empathize, Define, Ideate, Prototype, and Test stages. The application is designed based on the Flutter framework with imaging SQLite local database and Firebase synchronization. The design testing involves functional testing and non-functional testing (Heuristic Evaluation, Cognitive Walkthrough, and First-Click Testing). The results indicate that all functional requirements are met, and the design is considered intuitive with a First-Click success rate of 91.6%, exceeding the feasibility threshold of 87%. This study concludes that the digital text-based Rawi application design successfully enhances accessibility and user experience through personalization features such as font resizing, advanced searching, as well as bookmark and favorite management.